Diagnosa Penyakit Rabbit Haemorrhagic Disease dengan Menggunakan Kombinasi Metode VCRIS dan CF - Ningtyas, Alyiza Dwi (Jurnal Sains dan Teknologi Informasi, 2025)
One of the rabbit diseases in the respiratory system is caused by a virus called rabbit hemorrhagic disease. Rabbit hemorrhagic disease is a disease caused by a virus that attacks the respiratory system of rabbits. For this reason, a system is needed that is designed to be able to imitate the expertise of an expert in answering questions and solving a problem according to the expert's knowledge which is entered into a computer system. The development of artificial intelligence technology that has occurred has enabled expert systems to be applied in detecting disease using programming languages. One of them is providing information about various problems, especially rabbit hemorrhagic disease. The expert system method used is a combination of the Variable Centered Intelligent Rule System (VCIRS) and Certainty Factor (CF) methods, which is one solution that can display the final results of several rabbit haemorrhagic disease diagnoses. With the facilities provided to users, it is possible to use this system according to their individual needs. Users are given the convenience of finding out information about the symptoms of rabbit hemorrhagic disease and its prevention.